PENGARUH PEMBERIAN ZAT PENGATUR TUMBUH (ZPT) AIR KELAPA MUDA DAN LAMA PERENDAMAN TERHADAP VIABILITAS BENIH PADI VARIETAS LOKAL - Budiyono, Budiyono; Saputra, Whin Themas Mico; Chairani, Nadia (Cangkok, 2024)
Currently, Indonesia still often faces food problems, such as the conversion of agricultural land into industrial and residential areas which causes a decrease in rice productivity. High-quality seeds are seeds that have high germination. One of the drivers in increasing seed viability is the use of Growth Regulatory Substances (ZPT) such as those contained in young coconut water which are needed for plant development and growth. Young coconut water also contains organic compounds such as vitamin C, B vitains, auxin hormones, gibberellins and cytokinins. The experimental design used in this study used a completely randomized design (CRD) with a factorial pattern. The factors studied were the concentration of coconut water (A) and duration of immersion in coconut water (L). The provision of young coconut water had a significant effecton growth potential, germination rate, growth speed, and growth simultaneously but had a very significant effect on the weight of the wet stover, and had no significant effect on the dry stover, weight. Growth speed, and growth simultaneously but very significant effect on the weight of the wet stover, and no significant effect on the weight of the dry stover